Ukuran Perusahaan dan Tax Avoidance: Peran Moderasi Kepemilikan Institusional - Lestari, Heppy Widya; Subiyantoro, Edy; Pangastuti, Dyah Ani (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
This research explores the influence of firm size on tax avoidance and the moderating role of institutional ownership in the manufacturing sector, specifically in the food and beverage subsector. The manufacturing sector plays a crucial role in providing essential food and beverage products to society. In a dynamic business environment with stringent tax regulations, tax avoidance practices have become a significant concern. The study aims to understand how firm size affects tax avoidance behavior and how institutional ownership moderates this relationship. Findings will contribute insights for better tax planning strategies, compliance, and governance in the food and beverage manufacturing industry. The research results show that company size has a significant positive effect on the tax avoidance variable in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange.